2017
DOI: 10.1080/21688370.2017.1336194
|View full text |Cite
|
Sign up to set email alerts
|

Time- and dose-dependent claudin contribution to biological functions: Lessons from claudin-1 in skin

Abstract: There are many types of biologic compartments in the body. Tight junctions (TJs) function to create a dynamic paracellular barrier to separate these compartments and maintain homeostasis. The TJ component claudin-1 is the major transmembrane protein responsible for forming the paracellular barrier in the epidermis; other claudins in the epidermis include claudin-3, -4, -12, -23 and -25. Accumulating evidence points to a relationship between claudin-1 and skin diseases; for example, a decrease in claudin-1 is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…When comparing the mouse skin epithelium to palate epithelium, we identified Cldn1 as the most over expressed TJ gene in skin, with Cldn8 being most over expressed in the palate. High Cldn1 expression observed in the tail epidermal cell population is consistent with previous reports on this TJ gene as being one of the major transmembrane proteins involved in forming the epidermal paracellular barrier in skin [29]. Interestingly, high Cldn8 expression has been observed in clinical cancer cell samples relative to benign controls and was shown to promote a pro-migratory and proliferative phenotype in multiple studies [30,31] which is in line with the more proliferative phenotype observed in oral epithelium.…”
Section: Discussionsupporting
confidence: 90%
“…When comparing the mouse skin epithelium to palate epithelium, we identified Cldn1 as the most over expressed TJ gene in skin, with Cldn8 being most over expressed in the palate. High Cldn1 expression observed in the tail epidermal cell population is consistent with previous reports on this TJ gene as being one of the major transmembrane proteins involved in forming the epidermal paracellular barrier in skin [29]. Interestingly, high Cldn8 expression has been observed in clinical cancer cell samples relative to benign controls and was shown to promote a pro-migratory and proliferative phenotype in multiple studies [30,31] which is in line with the more proliferative phenotype observed in oral epithelium.…”
Section: Discussionsupporting
confidence: 90%
“…3). Cldn-1 has previously been shown to be indispensable for the barrier function of mammalian skin, where mutations in this protein resulted in multiple skin defects and increased epidermal paracellular permeability (Hadj-Rabia et al, 2004;Brandner, 2009;Kirschner et al, 2009;De Benedetto et al, 2011;Günzel and Yu, 2013;Kirchmeier et al, 2014;Tokumasu et al, 2017). Cldn-1-deficient mice died shortly after birth as a result of evaporative water loss through the skin, implying that Cldn-1 may act as a water barrier in mammalian skin (Furuse et al, 2002).…”
Section: Effect Of Bd Infection On Cldn-1 Ocln and Tric Abundancementioning
confidence: 99%
“…Continuous Claudin-based TJs are present in the epidermis and these particular TJs are crucial for the barrier function of mammalian skin ( 17 ). In addition, Claudin-1 and -4 are involved in the pathogenesis of skin lesions ( 18 - 20 ). How Claudin-1 and -4 are regulated in response to ATRA is largely unknown.…”
Section: Introductionmentioning
confidence: 99%